Poetic licence to write resistance: women resisting intimate partner violence through poetry. (1st August 2019) - Donovan, Andrea Merriam; Dubrasky, Danielle; Sorensen, Scott; Corser, Grant
Abstract : The poetry therapy programme discussed describes work alongside members of a rural women's support group addressing intimate partner violence. This approach contributes to social work theory/practice by expanding understandings of how women resist violence and affirms a tenet of Response-Based Practice: 'alongside each history of violence there runs a parallel history of prudent, determined, and often creative resistance' (Wade, 1997: 23). This approach to creative group-based work supports 'positive social responses' to women resisting intimate partner violence, expanding the ways in which social workers can respond to survivors of violence (Richardson and Wade, 2009: 209). Subtle and safer responses to violence are undervalued by dominant therapeutic practices. Response-Based Practice maintains that violence is resisted on a spectrum and that less noticeable forms of resistance are well reasoned and maintain dignity. This article describes how combining poetry therapy with Response-Based Practice can disrupt notions of resistance as solely outwardly expressed and large-action-oriented.